A framework for relating business constraints to information systems - Carver, Andrew; Morgan, Tony (Springer Berlin Heidelberg, 2012)
Many previous attempts at classifying business rules rely on over-simplistic frameworks that conflate business concerns with technical features. Such frameworks hamper trace ability between information systems and business needs and can lead to paradoxes that are difficult to reconcile. This paper offers an alternative framework for business constraints, including those that can be embodied in information systems. We assume that such information systems are likely to be automated, but the proposed scheme does not rely on any automation. The paper uses several examples to illustrate the issues that arise with current classification frameworks and the benefits that a more realistic framework can provide.